1996
DOI: 10.1039/cc9960002083
|View full text |Cite
|
Sign up to set email alerts
|

A highly active alkane dehydrogenation catalyst: stabilization of dihydrido rhodium and iridium complexes by a P–C–P pincer ligand

Abstract: The novel P-C-P pincer complex, [IrH2{C6H3(CH2PBuf2)2-2,6}] has long-term stability at 200 "C and catalyses the transfer dehydrogenation of cyclooctane to cyclooctene at the rate of 12 turnovers min-'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
273
3
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(286 citation statements)
references
References 22 publications
7
273
3
3
Order By: Relevance
“…by hydride and formation of 258 has been accomplished originally by using KH, 408 later also with LiBEt 3 H, 409 or simply with a non-nucleophilic base in the presence of an alkane like cyclooctane (coa). 410 The latter procedure affords an equilibrium between 258 and an iridium(I) complex comprising the PCP pincer ligand and coe.…”
Section: Scheme 101mentioning
confidence: 99%
“…by hydride and formation of 258 has been accomplished originally by using KH, 408 later also with LiBEt 3 H, 409 or simply with a non-nucleophilic base in the presence of an alkane like cyclooctane (coa). 410 The latter procedure affords an equilibrium between 258 and an iridium(I) complex comprising the PCP pincer ligand and coe.…”
Section: Scheme 101mentioning
confidence: 99%
“…A number of early reactivity studies showed that the chemistry of square-planar late-transition-metal pincer complexes of this type is particularly rich ([2] and references therein). Subsequent studies have demonstrated the utility of such complexes in Lewis acid catalysis [2a] [3], Heck reactions [4], Kharasch additions [5], catalytic dehydrogenation [6], transfer hydrogenation [7], and investigations of CÀH and CÀC oxidative addition reactions ( [8] and references in [8a]).…”
mentioning
confidence: 99%
“…1 With the recent development of effective catalysts for dehydrogenation that involve Rh, or more especially Ir, complexes related to compound 1, interest in their application has been heightened. 2 Among the factors that contribute to their reactivity in the critical C-H activation step will be the chelate bite angle and the electronic character of both the s-and n-bonding entities. Synthesis and complexation chemistry of a higher homologue 2 based on cycloheptatriene has already been reported.…”
mentioning
confidence: 99%